Seismic shear and acceleration demands in multi-storey cross-laminated timber buildings. (1st November 2019) - Demirci, Cagatay; Málaga-Chuquitaype, Christian; Macorini, Lorenzo
Highlights: First systematic assessment of base shears, inter-storey shears and peak accelerations in multi-storey CLT buildings. Shear and acceleration demands depend significantly on the mean period of the ground-motion. Regression models provided for the estimation of shear modification factors and acceleration amplification factors. Larger levels of plasticity (greater q factors or higher panel fragmentation) lead to lower relative shear demands. Accelerations strongly influenced by higher modes and degree of CLT panel subdivision. Abstract: A realistic estimation of seismic shear demands is essential for the design and assessment of multi-storey buildings and for ensuring the activation of ductile failure modes during strong ground-motion. Likewise, the evaluation of seismic floor accelerations is fundamental to the appraisal of damage to non-structural elements and building contents. Given the relative novelty of tall timber buildings and their increasing popularity, a rigorous evaluation of their shear and acceleration demands is all the more critical and timely. For this purpose, this paper investigates the scaling of seismic shear and acceleration demands in multi-storey cross-laminated timber (CLT) buildings and its dependency on various structural properties. Special attention is given to the influence of the frequency content of the ground-motion. A set of 60 CLT buildings of varying heights representative of a wide range of structural configurations is subjected to a large dataset of 1656 real earthquake records. It is demonstrated that the mean period ( T m ) of the ground-motion together with salient structural parameters such as building aspect ratio ( λ ), design force reduction factor ( q ) and panel subdivision ( β ) influence strongly the variation of base shear, storey shears and acceleration demands. Besides, robust regression models are used to assess and quantify the distribution of force and acceleration demands on CLT buildings. Finally, practical expressions for the estimation of base shears, inter-storey shears and peak floor accelerations are offered.